Married to the military : the employment and earnings of military wives compared with those of civilian wives - Hosek, James R. (Rand, 2002)
Today's military is a military of families; many service members are married, and many of their spouses work and contribute to family income. But military wives earn less than civilian wives, and this study seeks to understand why. The authors find that military wives, knowing they are likely to move frequently, are willing to accept jobs that offer a lower wage rather than to use more of their remaining time at a location to find a higher-wage job. Compared with civilian wives, military wives tend to work somewhat less if they have young children but somewhat more if their children are older.